Aspartame, Behavior, and Cognition in ADD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The effects of aspartame (34 mg/kg/day for 2 weeks) on the cognition, behavior, and monoamine metabolism of 15 children with a history of ADD were evaluated at the Yale University School of Medicine, using a randomized, double-blind, placebo-controlled crossover study design.